Pregnancy and venous thrombosis (Hematology Meeting Reports, 2009)
Epidemiology and pathophysiology The risk of venous thromboembolism (VTE) during pregnancy and puerperium is markedly higher than in non-pregnant women of comparable age. In developed countries, where the mortality for other causes has been reduced, VTE is currently one of the most common cause of maternal mortality.1,2 The incidence of VTE events is about 1/1000 women-y of pregnancy and more 7 out of 1000 women-y post partum; this represents a 2.5-fold increase in the risk of VTE during pregnancy and 20-fold increase during puerperium compared to non-pregnant women of comparable age.3 The incidence of VTE in the United States has been estimated between 0.5 and 0.7 events/1000 deliveries for deep vein thrombosis (DVT), and between 1:2500 to 1:10,000 deliveries for pulmonary embolism (PE).4